Proyecto de evaluación sobre la creación de una microempresa para la instalación de airbags en vehículos - Duarte Tobar, Milton E. (2011)
In the present project realizes a study of market and financial feasibility for the implementation of a microempresa for the installation of Airbags in vehicles, it would help to the drivers to diminish the risk of grave injuries in the head, cervical and high part of the trunk to the moment to have some impact the vehicle. To world wide level some countries are changing the laws so that the use of the Airbag in the vehicles was totally compulsory. Inside the study of market consider several appearances like the one of the park automotor and the index of accidents that reflect the need to install the Airbag in the vehicles. Regarding the financial analysis here detail all the cost that take part in this project and also the income that expect obtain what complement with the analyses for the certification rentable of the project.